Women a world report. (Methuen London Ltd, 1985)
A book which reports on the lives of women throughout the world at the end of the United Nations' Decade for Women. It combines an analysis of the latest facts and figures, especially collected from almost every country in the world, with a series of essays by some of the world's most important contemporary women writers. a unique synthesis of facts and personal impressions, the book stands as a landmark in our understanding of women's role in the world today.